Percepção e atitude dos Agentes Comunitários de Saúde relacionados à saúde da pessoa idosa: revisão da literatura - Bazani, Paula Lorena Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Family Health Strategy is a health policy developed by the Brazilian government for the promotion and prevention of public health. Counting with a multiprofessional team, actions are elaborated and carried out in the population of the municipalities that have the program. One of the social actors belonging to the team is the Community Health Worker (CHW), being the main link between the population and the health system, responsible for collecting data from this community and disseminating health knowledge. The objective of the study was to obtain information about the agents' perception and attitude regarding the health of the elderly, both in the buccal and general. Information was collected through a bibliographic survey carried out in specialized books and scientific papers, both nationally and internationally, in the databases Scielo, Pubmed, Lilacs and Medline. 67 studies were performed, of which 43 were excluded because they were not considered adequate for our purpose and 14 were used. After analyzing the work, we found that the greatest problem is the lack of training of the workers, who find it difficult to act, since they lack the necessary information to effectively carry out health promotion and prevention actions

A Estratégia Saúde da Família é uma política de saúde desenvolvida pelo governo brasileiro para a promoção e prevenção em saúde pública. Contando com uma equipe multiprofissional, ações são elaboradas e realizadas na população dos municípios que possuem o programa. Um dos atores sociais pertencentes a equipe é o Agente comunitário de Saúde (ACS), sendo o principal elo entre a população e o sistema de saúde, responsável pelo recolhimento dos dados dessa comunidade e disseminação de conhecimentos em saúde. O objetivo do trabalho foi obter informações sobre a percepção e atitude dos agentes em relação à saúde da pessoa idosa, tanto da parte bucal quanto geral. Foram colhidas informações através de um levantamento bibliográfico realizado em livros especializados e trabalhos científicos, tanto nacionais quanto internacionais, nas bases de dados Scielo, Pubmed, Lilacs e Medline. 67 trabalhos foram levantados, sendo que 60 foram excluídos por não serem considerados adequados ao nosso objetivo e 7 foram utilizados. Após analisar os trabalhos, constatamos que o maior problema existente é a falta de capacitação dos trabalhadores, que encontram dificuldades de atuação, pois falta-lhes as informações necessárias para realizar de forma efetiva as ações de promoção e prevenção em saúde
Keywords: Agentes comunitários de saúde; Idosos; Envelhecimento; Community health aides